Validating the Teacher Collective Efficacy Scale in the Cambodian Context: Exploratory and Confirmatory Factor Analyses - Khan, Somphors; Mok, Sarom; Sam, Rany; Em, Sereyrath (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the Study: This study is part of a bigger quantitative research design aiming to extract the initial teacher collective efficacy and convergent validity. Methodology: This study collected data from 619 teachers in secondary resource schools. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were employed using SPSS and Mplus software to assess validity and reliability. Main Findings: EFA identified two factors with eigenvalues of 5.13 and 1.54, accounting for 55.58% of the variation in teacher collective efficacy. The EFA results showed a single-dimensional factor representing teacher collective efficacy. CFA confirmed that all nine indicators had strong, statistically significant loadings (p < 0.001) ranging from 0.65 to 0.78. Fit indices (CFI = 0.97, TLI = 0.96, SRMR = 0.028, RMSEA = 0.057) indicated a very good model fit, supporting the construct validity of the scale. Novelty/Originality of This Study: This study advances knowledge by validating the measurement of teacher collective efficacy through rigorous statistical analysis. It provides empirical evidence supporting the reliability and validity of the scale, contributing to a better understanding of collective efficacy in secondary resource schools.